US monetary policy and global banking flows - Lee, S; Bowdler, C (Elsevier, 2020)
This note investigates the impact of US monetary policy on US global bank leverage and cross-border US dollar denominated banking flows, using US monetary policy shocks identified based on narrative sources and the Federal Reserve’s Greenbook forecasts (Romer and Romer, 2004). Compared to Bruno and Shin (2015), who employ standard recursive monetary policy identification techniques, we find that leverage declines more quickly and to a much larger extent after a monetary tightening, suggesting that declines in the availability of debt finance play a significant role in the propagation of monetary policy via the banking system. The decline in international flows of dollar denominated bank funding is also larger using the externally identified monetary policy measure, as is the degree of US dollar appreciation. By expanding the baseline model into bilateral VARs for 36 countries, we find that the retrenchment of cross-border banking flows after US monetary contraction is much larger in response to the externally identified monetary policy shocks, which is consistent with the results of the aggregate model. By looking at country groups, it is observed that banking outflows after US monetary contraction are more pronounced in the case of emerging market economies than in the case of advanced economies.